Effect of pulmonary exacerbations treated with oral antibiotics on clinical outcomes in cystic fibrosis. Issue 4 (18th August 2016) - Stanojevic, Sanja; McDonald, Alexandra; Waters, Valerie; MacDonald, Sarah; Horton, Eric; Tullis, Elizabeth; Ratjen, Felix
Abstract : Background: Despite extensive knowledge regarding the effect of pulmonary exacerbations treated with intravenous antibiotics on clinical outcomes in cystic fibrosis (CF), there is little known about the role of milder pulmonary exacerbations treated with oral antibiotics (oPEx). Methods: This was a retrospective cohort study of patients with CF followed at the Hospital for Sick Children and St. Michael's Hospital from 2009 to 2014. We evaluated the effect of oPEx on short-term clinical outcomes as the proportion of oPEx events in which 100% or 90% of baseline FEV1 % predicted was recovered at the end of treatment. We then examined the association of the number of oPEx events in the past 12 months on lung function (FEV1 % predicted) and nutritional status (body mass index (BMI) z-score) using a mixed-effects model. Results: There were a total of 2608 oPEx events in 570 subjects during the study period. In over half (53.4%) of oPEx events, lung function was already at 90% or higher of baseline FEV1 at the initiation of oral antibiotic therapy and 82% were at 90% or higher of baseline FEV1 at follow-up. In individuals with CF, one or more oPex events in the previous 12 months were associated with decreased FEV1 compared with 12 months periods without oPex events. When the cumulative effect of oPExs on lung function was examined over the entire study period, patients with six or more oPEx events had the steepest rate of FEV1 decline. oPEx events were not associated with changes in BMI. Conclusions: oPEx events are associated with short-term loss of FEV1 and have a negative effect on lung function over time.